2021
DOI: 10.1038/s41598-021-96710-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing reveals possible host species adaptation of Streptococcus dysgalactiae

Abstract: Streptococcusdysgalactiae (SD) is an emerging pathogen in human and veterinary medicine, and is associated with several host species, disease phenotypes and virulence mechanisms. SD has traditionally been divided into the subspecies dysgalactiae (SDSD) and subsp.equisimilis (SDSE), but recent molecular studies have indicated that the phylogenetic relationships are more complex. Moreover, the genetic basis for the niche versatility of SD has not been extensively investigated. To expand the knowledge about virul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
17
1
1
Order By: Relevance
“…Furthermore, a modest number of ST were identified among the 89 sequenced SDSD isolates from 27 geographically spread farms, and one ST (ST453) was identified in 15 different herds. In a previous study, we sequenced SDSD from different species and found that SDSD delineated according to host species (Porcellato et al, 2021). By documenting that a few SDSD genotypes are more prevalent and can be found in geographically spread bovine dairy herds, our study supports the existence of bovine-adapted SDSD.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, a modest number of ST were identified among the 89 sequenced SDSD isolates from 27 geographically spread farms, and one ST (ST453) was identified in 15 different herds. In a previous study, we sequenced SDSD from different species and found that SDSD delineated according to host species (Porcellato et al, 2021). By documenting that a few SDSD genotypes are more prevalent and can be found in geographically spread bovine dairy herds, our study supports the existence of bovine-adapted SDSD.…”
Section: Discussionsupporting
confidence: 75%
“…The isolates had been collected by freezing the first SDSD isolates obtained from clinical mastitis (n = 5) and subclinical mastitis (n = 5) every month between April and November 2019. Of the 90 sequenced isolates, 20 have been described previously (Porcellato et al, 2021). All genomes are available at DDBJ/ENA/Gen-Bank under the BioProject PRJEB42928.…”
Section: Genome Sequencing Of Sdsd Isolates and Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene shares greater than 70% identity between bovine SDSD and Streptococcus equi. Among the bovine SDSD genomes, the mga gene and an open reading frame (ORF) previously identified as homologous to S. pyogenes M proteins ( Porcellato et al, 2021 ) were observed upstream of the cspZ gene. The mga gene of bovine SDSD shares approximately 70% identity with S. pyogenes , but the ORF is around 40% identical to the S. pyogenes sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The subspecies SDSE, initially regarded as human commensal bacteria ( Suzuki et al, 2011 ), is now recognized to be an important human pathogen, causing several infections, including bacteremia, cellulitis, endocarditis, peritonitis, septicemia, pneumonia, pharyngitis, and toxic shock syndrome, similar to those caused by S. pyogenes ( Brandt and Spellerberg, 2009 ; Bruun et al, 2013 ; Hagiya et al, 2013 ; Fuursted et al, 2016 ). Additionally, β-hemolytic isolates from animal hosts have been frequently identified as SDSE ( Acke et al, 2015 ; Pinho et al, 2016 ; Oh et al, 2018 , 2020 ; Porcellato et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%